Hemorrhaging laparoscopic partial nephrectomy — feasibility of a novel simulation model - Lusty, Avril J.; Bleackley, Joanne; Roberts, Matthew; Watterson, James; Raîche, Isabelle (Canadian Urological Association Journal, 2021)
Introduction: Intraoperative surgical complications pose significant potential risks to patients. Uncontrolled bleeding during laparoscopic partial nephrectomy is one such event that requires collaboration and communication between surgical team members. We developed and evaluated a multidisciplinary surgical simulation scenario and model of intraoperative hemorrhage during a laparoscopic partial nephrectomy to facilitate the practice of these crucial non-technical skills. Methods: A simulation scenario using a novel, titratable, bleeding partial nephrectomy model was developed. The operating room simulation consisted of an intubated mannequin placed in the lateral decubitus position and laparoscopic renal model. The multidisciplinary simulation scenario included anesthesia and urology residents and progressed from bleeding to a pulseless electrical activity arrest. The degree of renal model bleeding was modified based on the progression of the urology resident. After the scenario, participants were debriefed and completed a post-simulation survey assessing: 1) their perception of the simulated scenario; and 2) their teaching of non-technical skills in their residency training. Results: The porcine model was successfully reproduced for nine consecutive weeks and functioned well to simulate bleeding from a laparoscopic partial nephrectomy site; the bleeding was able to be titrated based on resident progression and excision of the simulated tumor. All residents stated the scenario was valuable to assess and improve non-technical surgical skills and that their exposure to practice non-technical skills in their existing curriculum could be improved. Conclusions: Simulating an intraoperative bleeding partial nephrectomy, combined with an intraoperative crisis scenario, is a feasible, immersive, and reproducible model and can challenge residents’ non-technical skills.